2006
DOI: 10.2353/jmoldx.2006.050065
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Apparent Homozygous 3120G>A Cystic Fibrosis Mutation on a Routine Carrier Screen

Abstract: A 28-year-old Caucasian female with no personal or family history of cystic fibrosis (CF) presented for preconception counseling and screening. Cystic fibrosis transmembrane conductance regulator (CFTR) mutation analysis using the Inno-LiPa CFTR assay revealed lack of hybridization for both the wild-type and mutant oligonucleotides for 3120؉1G>A. This region was sequenced, and an apparent homozygous 3120G>A mutation was detected. Additional testing revealed an abnormal sweat chloride (77 mmol/L). Review of sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In Kuwaiti population, 55% of the CF patients exhibited the delF508, G542N and p.W1282X while 24% of cases showed c.1548delG, c.I1234V and 3120+1G>A [15]. In another study, the 3120+1G>A was a rare mutation, been detected in 3 patients along with another patient having an additional mutation ∆F508 on the other allele [16]. Our results showed 4 patients with the 3120+1G>A mutation only and one patient carrying both the 3120+1G>A and ∆F508 mutations.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In Kuwaiti population, 55% of the CF patients exhibited the delF508, G542N and p.W1282X while 24% of cases showed c.1548delG, c.I1234V and 3120+1G>A [15]. In another study, the 3120+1G>A was a rare mutation, been detected in 3 patients along with another patient having an additional mutation ∆F508 on the other allele [16]. Our results showed 4 patients with the 3120+1G>A mutation only and one patient carrying both the 3120+1G>A and ∆F508 mutations.…”
Section: Discussionsupporting
confidence: 46%
“…More interestingly, a previous study including UAE and Oman populations showed that all patients were homomzygous for the single mutation p.S549R. Another study conducted for only 16 Omani patients revealed that 69% from Bedouin descent were found to have the p.S549R (T-G) mutation, while 12.5% (two), from Baluch decent had the ΔF508 mutation, and the remaining patients were negative for the mutations [4,10]. All these studies are in agreement with the findings of our present study.…”
Section: Discussionmentioning
confidence: 91%
“…The probes correspond to the normal and mutated alleles, covering 36 most frequent European CFTR mutations. The procedure was performed as indicated by the manufacturer (InnoGenetics, Ghent, Belgium; see also [35] ).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained HEK293 cells stably expressing a minigene containing the full length CFTR coding sequence carrying a c.2988G>A mutation and flanking introns ( Supplementary table 3) 60 . This mutation is associated with abnormal CFTR function and causes a mild form of CF (MIM# 219700) 61 . Treatment with BPN-15477 increased exon 18 inclusion by 10%, confirming our CNN model prediction ( Fig.…”
Section: Experimental Validation Of New Therapeutic Targets For Bpn-1mentioning
confidence: 99%